The Meaning of Cultural Accounting in the Peraq Api Tradition: Ethnographic Study in Lombok - Dewi, Yunita Asmara; Sokarina, Ayudia (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to find out the meaning of cultural accounting in the peraq api tradition and how accounting practices are applied in the peraq api tradition in Selebung village, by finding out how the Sasak people interpret peraq api which has been a tradition from the past until now. This research uses interpretive and ethnographic paradigms as research methodology. Data collection techniques were carried out using interviews, observation and documentation. The research results show that cultural accounting in the Peraq Api tradition has the meaning of gratitude and responsibility. Gratitude is expressed in happiness and thanks for the birth of a child, while responsibility is emphasized in wise financial management, transparency and accountability. Cultural accounting in this tradition reflects Sasak noble values, such as mutual cooperation, social care, kinship and compassion. These findings indicate that cultural accounting plays an important role in preserving Sasak culture and strengthening cultural identity. This tradition also shows how the Sasak people use accounting to manage resources sustainably and ensure the welfare of their community.